Theranostics in surgical oncology - Stättner, Stefan; Soreide, Kjetil; Hallet, Julie; Grana, Chiara Maria; Partelli, Stefan; Herrmann, Ken; Brandl, Andreas (European journal of surgical oncology, 2026)
Theranostics is a method where molecules that target surface structures in tumors are coupled with different radioisotopes, allowing them to bind to tumor cells for detection (diagnostic) and elimination (therapeutic). In the case of neuroendocrine tumors (NET), peptides targeting somatostatin receptors (SSTR) are most commonly used for this purpose. These peptides are, for example, coupled with 68Ga for diagnostic and 177Lu for therapeutic purposes. This allows SSTR-positive tumors to be detected with high sensitivity and treated effectively, which is particularly beneficial in cases where surgery (alone) is not feasible. However, theranostic procedures can also be used to guide surgical procedures or - in the context of a neoadjuvant approach - increase resectability. Other therapies currently in development aim to increase antitumor effectiveness or aim to combat tumors which are resistant to other radiopharmaceutical therapies (RPT) using new isotopes and SSTR-targeting peptides or combining RPT with other drugs. Modern radiological diagnostics, as well as the production and use of radiopharmaceuticals, require costly equipment and specialized procedures and are therefore not accessible to most patients around the world. However, the expansion of the repertoire of studied and approved theranostics promises to make these highly effective treatments available to more patients. The following review intends to provide an overview of current questions about theranostics with relevance to surgical oncology.